Outcome of general anaesthesia by laryngeal mask airway (LMA) in ophthalmic surgery in the national institute of ophthalmology and hospital, Dhaka - Quadir, Kanijun Nahar; Khosal, AM Alamgir; Alam, Fakrul; Ali, SM Idris; Ahsan, Mian Md Abul; Alam, Sovona (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Patient is very safe under general anaesthesia with laryngeal mask airway intra and post operatively in ophthalmic surgery. Methods Different ophthalmic procedures and surgery were done on different age group from five months to fifty years with ASA grade I and II under general anaesthesia by laryngeal mask airway (LMA) to see the haemodynamic status and other parameters during operation and post operative recovery period. Results Total number of ophthalmic surgery under G/A was 1814. General anaesthesia by orothracheal intubation was given only in twenty five (25) patients and general aneasthesia was given by Laryngeal mask airway insertion in 1789 patients. Complications occur in Laryngeal mask airway group patients only in 8 patients. Percentage of safe LMA insertion was 99.55% and percentage of complication was only 0.45%. Operation time ranges from few minutes to two hours. General aneasthesia through laryngeal mask airway insertion make the procedures easy and safe for the patients except minimum percentage of complications. Conclusion Laryngeal mask airway causes less changes of haemodynamic parameter. LMA is very effective in the spontaneously breathing patient. During operation patients become stable and no rise of intraocular pressure and on reverse the patient become smooth with less secretion, no spasm, no cough and no vomiting. JBSA 2012; 25(1): 28-31